PENDEKATAN STEAM BERBASIS KONTEN LOKAL UNTUK MENJADIKAN MATEMATIKA BERMAKNA DAN MENYENANGKAN - Mubarik Mubarik; Rahma Nasir; Dewi Ulfiana; Desti Desti (HISTOGRAM: Jurnal Pendidikan Matematika, 2022)
At this time students must be introduced to learning mathematics that is meaningful, fun and not boring. Through STEAM learning, teachers can create learning that is directly related to everyday life so as to create fun learning that can increase student motivation to learn. This study aims to find out and describe how a STEAM approach based on local content can make mathematics meaningful and fun. This type of research is descriptive with a qualitative approach. The results of this study indicate that there are several cultural riches in the Donggala district that can be explored and used as alternative media for learning mathematics, including banava batik with coffee motifs, clove motifs and traditional motifs. Integrating local content in the STEAM approach can show students that mathematics is not an abstract thing that has no relevance to life, but is very closely related to real life. This learning will make mathematics which is abstract and tends to be boring become more real for students